2017
DOI: 10.1007/978-1-4939-7380-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Immunoprecipitation from Mouse Embryonic Tissue or Adherent Cells in Culture, Followed by Next-Generation Sequencing

Abstract: Chromatin immunoprecipitation (ChIP) is considered the method of choice for characterizing interactions between a protein of interest and specific genomic regions. It is of paramount importance in gene-regulation studies, as it can be used to map the target regions of sequence-specific transcription factors and cofactors, or histone marks that characterize distinct chromatin states. ChIP can be used directly to probe interactions with candidate regions (ChIP-PCR), or coupled to Next-Generation Sequencing (ChIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Chromatin factors and histone modifications are well conserved from worms to humans (Wenzel et al., 2011), and research in worms has identified numerous histone modifications, chromatin factors, and transcription factors that are associated with development, aging, and more (Cui & Han, 2007; González‐Aguilera et al., 2014). ChIP‐seq, which allows genome‐wide localization analysis of proteins of interest and has been utilized in numerous organisms (Chen et al., 2018; Ostrow et al., 2015; Pu & Lee, 2020; Sen et al., 2021; Soares & Castro, 2018; Sullivan & Santos, 2020; Tran et al., 2012), has been less commonly applied in C. elegans due to the significant undertaking of this experiment. For instance, a recently published optimized ChIP‐seq protocol recommends using ∼600,000 worms for one experiment, necessarily requiring specialized equipment and numerous complex steps to produce quality C. elegans ChIP‐seq libraries (Sen et al., 2021).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin factors and histone modifications are well conserved from worms to humans (Wenzel et al., 2011), and research in worms has identified numerous histone modifications, chromatin factors, and transcription factors that are associated with development, aging, and more (Cui & Han, 2007; González‐Aguilera et al., 2014). ChIP‐seq, which allows genome‐wide localization analysis of proteins of interest and has been utilized in numerous organisms (Chen et al., 2018; Ostrow et al., 2015; Pu & Lee, 2020; Sen et al., 2021; Soares & Castro, 2018; Sullivan & Santos, 2020; Tran et al., 2012), has been less commonly applied in C. elegans due to the significant undertaking of this experiment. For instance, a recently published optimized ChIP‐seq protocol recommends using ∼600,000 worms for one experiment, necessarily requiring specialized equipment and numerous complex steps to produce quality C. elegans ChIP‐seq libraries (Sen et al., 2021).…”
Section: Commentarymentioning
confidence: 99%
“…The genome‐wide DNA‐binding profile of histone marks, transcription factors, and chromatin factors can reveal not only mechanisms of transcriptional regulation, but also complex interactions between chromatin‐associated proteins, for instance, whether a certain transcription factor is necessary for recruitment of a chromatin modifier. The most commonly used approach to obtain such profiles in a genome‐wide manner is chromatin immunoprecipitation followed by sequencing (ChIP‐seq), which remains a staple in the chromatin biology field to this day and has been widely applied in organisms from yeast to humans (Chen, Bhadauria, & Ma, 2018; Ostrow, Viggiani, Aparicio, & Aparicio, 2015; Pu & Lee, 2020; Sen, Kavšek, & Riedel, 2021; Soares & Castro, 2018; Sullivan & Santos, 2020; Tran, Gan, & Chen, 2012). ChIP approaches are often limited in their resolution, however, and require large amounts of chromatin as starting material and high sequencing depth to obtain a good signal‐to‐noise ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of the ChIP technique, new upgrades have been developed like the Re-ChIP method, in which two antibodies directed against two different antigens are used, one after the other, allowing the identification of DNA fragments where two protein factors are simultaneously bound; or the ChIP-on-ChIP variant, in which immunoprecipitated DNA is used as a probe to hybridize a slide containing fragments of genomic DNA (chips) leading to the identification of new targets (Figure H). Initially developed in yeast, ChIP-on-ChIP is today successfully applied to human systems. As mentioned above, the ChIP procedure constituted a fantastic improvement in the investigation of DNA–protein interactions both in vitro and in vivo . However, although this approach was born to be addressed to the identification of DNA target regions where a specific protein factor is bound to, in the last years, the attention was moved also toward the investigation of the additional proteins contemporarily present on the same oligonucleotide sequences.…”
Section: Chromatin Purification Methods Coupled With Mass Spectrometrymentioning
confidence: 99%